(untitled) (Sains Humanika, 2019)
The purpose of this article is to map the curriculum of Bachelor of Education in Geography programme with the Standard Document of Curriculum and Assessment (DSKP) in school. An analysis ofÂ document been implemented to examine the linkages between the geography curriculum at Universiti Pendidikan Sultan Idris (UPSI) towards the geography subject in Standard Curriculum for Secondary SchoolÂ (KSSM) of form one, two and three. The relationship matrix of paralleled themes was identified with the ATLAS.ti software. The themes examined comprised of physical geography, human geography and geographic skills. The results showed that 14 out of 16 courses of BED Geography were parallel with the Geography DSKP for form 1 to 3. There were eight topics in the DSKP of KSSM Geography that were not related in any Geography BED Instructional Plan, which involved two form 1 topics, titled Kedudukan and Lakaran Peta Malaysia; three form 2 topics, namely Telekomunikasi di Malaysia, Jenis dan Kemajuan Pengangkutan di Asia and Teknologi Hijau; and three form 3 topics, namely Tumbuh-Tumbuhan Semula Jadi di Malaysia, Hidupan Liar di Malaysia and Kitar Semula. The results showed that the university department need to improve the existing courses and there was a need for an addition of relevant courses to the Geography BED programme to aligned with the latest school curriculum. The findings of this study will be able to improve the education system at the university level in order to produce prospective geography teachers with the latest knowledge and the 21st century skills.